2022
DOI: 10.3390/pharmaceutics14061118
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Biodistribution and Pharmacokinetics Study of GMP-Grade Exosomes Labeled with 89Zr Radioisotope in Mice and Rats

Abstract: For the successful clinical advancement of exosome therapeutics, the biodistribution and pharmacokinetic profile of exogenous exosomes in various animal models must be determined. Compared with fluorescence or bioluminescence imaging, radionuclide imaging confers multiple advantages for the in vivo tracking of biomolecular therapeutics because of its excellent sensitivity for deep tissue imaging and potential for quantitative measurement. Herein, we assessed the quantitative biodistribution and pharmacokinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…The liver is a major organ where Exo-srIκB is delivered after intravenous injection [ 22 ]. Since exosome-mediated regulation of cellular responses of target cells is usually induced by endocytosis or membrane fusion [ 18 , 31 ], we next examined the transcriptional profiles of diverse hepatic cells to investigate the major target cell types for Exo-srIκB.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The liver is a major organ where Exo-srIκB is delivered after intravenous injection [ 22 ]. Since exosome-mediated regulation of cellular responses of target cells is usually induced by endocytosis or membrane fusion [ 18 , 31 ], we next examined the transcriptional profiles of diverse hepatic cells to investigate the major target cell types for Exo-srIκB.…”
Section: Resultsmentioning
confidence: 99%
“…Follow-up studies with Exo-srIκB have demonstrated that in vivo delivery of Exo-srIκB attenuates sepsis-associated organ damage and mortality, inflammatory responses related to preterm birth, and ischemia-reperfusion kidney injury in mice [ 19 , 20 , 21 ]. In addition, in vivo tracing of the biodistribution of zirconium-89 ( 89 Zr)-labeled Exo-srIκB in mice revealed a predominant delivery of Exo-srIκB to the liver after intravenous injection [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, the use of PET isotopes appears to be a better alternative to using 99m Tc due to the weak signal obtained from the tumor tissue, poor spatial resolution of SPECT, and difficulty providing reliable quantification. Among the possible PET isotopes, the following may be promising alternatives: radiometals with similar coordination chemistry, such as 64 Cu (t 1/2 = 12 h) and 89 Zr (t 1/2 = 78 h), or radioisotopes such as 124 I (t 1/2 = 4 days) [ 49 , 50 ]. Different strategies can improve the image resolution based on the increase in specific activity with radiolabeling.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of single photon emission computed tomography ( SPECT ) based detection of radioisotope-labeled OMVs has been used for in vivo tracing of OMVs of bacterial pathogens ( Berzosa et al., 2022 ). The technique of SPECT has excellent sensitivity for deep tissue imaging and allows quantitative measurements but is not superior in terms of spatial resolution and imaging time ( Choi et al., 2022 ). Positron emission tomography ( PET ) combines the advantages of SPECT while compensating for the deficiencies in spatial resolution and imaging time and has become a powerful tool for monitoring the biodistribution of vesicles in vivo ( Klein et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are many successful examples of imaging studies using 89 Zr-labeled bioactive molecules. The use of 89 Zr for radiolabeling EVs released from stem and cancer cells for in vivo tracking in mice, which assesses the quantitative biodistribution of vesicles in various tissues of animal models, also illustrates the general applicability of this radionuclide for in vivo PET long-term imaging ( Choi et al., 2022 ; Khan et al., 2022 ). It can easily label the surface of vesicles by using the iron carrier-derived chelator desferrioxamine ( DFO ) ( Zeglis and Lewis, 2015 ), which contains three chelating metal isohydroxamic acid groups and a primary amine group that couples biomolecules, allowing the formation of very stable complexes ( Feiner et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%